2018
DOI: 10.24141/2/2/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Nursing as a Profession

Abstract: The aim of the research was to determine the reasons why students enroll in undergraduate nursing studies and in what way the students' age, type of studies and familiarity with the profession affect their selection.In total, 156 first-and second-year nursing students between the ages of 18-30 participated in the study that was carried out at the University of Applied Health Sciences in Zagreb. The students had to answer multiple choice questions about their personal reasons for choosing nursing studies and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…Overall, our results show that burnout syndrome is prevalent among Croatian nursing students, which is in line with findings from previous studies conducted in other countries (18). This suggests that burnout is not only an issue for practicing nurses but also a significant concern for nursing students during their education because a large proportion of students cite idealism as a personal reason for choosing their studies (46.2%), regardless of whether they are full-time or part-time (19). The high prevalence of burnout in this population may have long-term consequences for the nursing profession, as it could negatively impact students' well-being, academic performance, and ultimately, their retention in the nursing workforce.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our results show that burnout syndrome is prevalent among Croatian nursing students, which is in line with findings from previous studies conducted in other countries (18). This suggests that burnout is not only an issue for practicing nurses but also a significant concern for nursing students during their education because a large proportion of students cite idealism as a personal reason for choosing their studies (46.2%), regardless of whether they are full-time or part-time (19). The high prevalence of burnout in this population may have long-term consequences for the nursing profession, as it could negatively impact students' well-being, academic performance, and ultimately, their retention in the nursing workforce.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our ndings, a study showed that students are exposed to professional values during their university education [23]. Several studies also reported that factors such as income and job security affected individuals' decision to enter nursing [42][43][44]. Another study reported the higher score of professional values among students who had considered congruence of nursing with their goals at the time of entering nursing [45].…”
Section: Discussionsupporting
confidence: 80%
“…The professional future, income, and economic status, increased interest in entering the field, and serving the people were the most common reasons for satisfaction with the field of nursing. Kolar et al declared that 46.2% of students chose nursing because of their desire for care and human ethics and 30.8% for financial reasons, such as financial stability and the high chance of finding a job, and in 88% of students, nursing was the first choice of study field (35). According to Mooney et al, the main reasons for choosing nursing were job security, fixed income, and easy to access to various job opportunities (36).…”
Section: Discussionmentioning
confidence: 99%